WHEN IS THE FUNCTIONS MEASURABLE? - Ro’zimova Sarvinoz Jumanazar qizi (TADQIQOTLAR.UZ, 2024)
In this article we explore under which conditions on the interior function the composition of functions is measurable. We also study the sharpness of the result by providing a counterexample for weaker hypotheses.